Case Report: Administration of Amniotic Fluid-Derived Nanoparticles in Three Severely Ill COVID-19 Patients - Mitrani, Maria Ines; Bellio, Michael A.; Sagel, Anthony; Saylor, Marie; Kapp, William; VanOsdol, Kathryn; Haskell, Gwendolyn; Stewart, Danique; Abdullah, Zanub; Santos, Ivan; Milberg, Julian; Arango, Alissa; et al. (Frontiers in Medicine, 2021)
Rationale/Objectives: A human coronavirus (HCoV-19) has caused the novel coronavirus disease (COVID-19) outbreak worldwide. There is an urgent need to develop new interventions to suppress the excessive immune response, protect alveolar function, and repair lung and systemic organ damage. Zofin (previously known as Organicell Flow) is a novel therapeutic that is derived from the soluble and nanoparticle fraction (extracellular vesicles and exosomes) of human amniotic fluid. Here within, we present the clinical outcomes after Zofin treatment in three critically ill patients suffering from severe, multi-organ complications induced by COVID-19 infection. All patients were diagnosed with COVID-19, developed respiratory failure, and were hospitalized for more than 40 days. Methods: Zofin was administered to patients concurrently with ongoing medical care who were monitored for 28-days post-therapy. SOFA score assessment, chest X-rays, and inflammatory biomarker testing was performed. Main Results: There were no adverse events associated with the therapy. The patients showed improvements in ICU clinical status and experienced respiratory improvements. Acute delirium experienced by patients completely resolved and inflammatory biomarkers improved. Conclusions: Primary outcomes demonstrate the therapy was safe, accessible, and feasible. This is the first demonstration of human amniotic fluid-derived nanoparticles as a safe and potentially efficacious therapeutic treatment for respiratory failure induced by COVID-19 infection.